Second trimester placental thickness: its’ correlation with gestational age, femur length and biparietal diameter - Ganjoo, Sandesh; Devgan, Shalini; Dev, Ghanshyam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Placental thickness (PT) is the easiest placental dimension to measure, yet little is known about the normal PT. The aim of this study was to determine the normal, sonographically measured PT in millimetre (mm) in the second trimester and to determine if this measurement can be adjusted for gestational age for that time and evaluate its relationship with femur length and biparietal diameter of the fetus. Methods: The study was a cross sectional observational study, recruiting 100 consecutive, singleton pregnancies, reporting for ultrasonography (USG) between 14 weeks and 24 weeks of gestation, having undergone at least one ultrasonogram in the first trimester, with known last menstrual period (LMP). The placental thickness was measured perpendicular to the uterine wall, through the placenta at the site of cord insertion. Results: The average age of study population was 24.96 with a standard deviation (SD) of 2.70 years with the minimum age being 18 years and maximum age being 32 years. Regression analysis yielded the following mathematical relationships between PT, Gestational age (GA), Biparietal diameter (BPD) and Femur length (FL) in the second trimester. Y(PT)= 0.9366x (Gestation age)+1.655, R2 = 0.7332; Y(PT)= 0.2872x(BPD)+6.9578, R2= 0.7314; Y(PT)=0.2995x(FL)+ 10.03, R2 = 0.6186 Conclusions: PT in present study showed a positive linear correlation with gestational age, FL and BPD in second trimester. Also, it can be concluded that PT may be used as a predictor of GA in women with unknown LMP.